2022
DOI: 10.1177/17479541211072966
|View full text |Cite
|
Sign up to set email alerts
|

Reference values for external and internal training intensity monitoring in professional male soccer players: A systematic review

Abstract: One of the possibilities for organising different studies and providing some reference values or benchmarks is to summarise all information. Such a possibility could help coaches and practitioners identify typical values based on specific conditions and eventually use benchmark values to compare players against The current systematic review was carried out to identify and summarise studies that have examined external and internal training intensity monitoring and to provide references values for the main measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…On the one hand, previous information highlighted that U-18 players from the present study showed higher levels of intensity. Although, the first team showed lower levels of total distance and high-intensity speed thresholds in matches than other studies conducted in first teams during training sessions, as highlighted by a recent systematic review [ 51 ]. This could be a concern considering that some studies showed that weekly training sessions did not express the same intensity as matches [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 98%
“…On the one hand, previous information highlighted that U-18 players from the present study showed higher levels of intensity. Although, the first team showed lower levels of total distance and high-intensity speed thresholds in matches than other studies conducted in first teams during training sessions, as highlighted by a recent systematic review [ 51 ]. This could be a concern considering that some studies showed that weekly training sessions did not express the same intensity as matches [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 98%
“…The scale varied from 0 to 10 A.U., where each value rated as: 0 –nothing to all; 0.5 –extremely weak; 1 –very weak; 2 –weak; 3 –moderate; 4 –somewhat strong; 5 –strong; 7 –very strong; and 10 –extremely strong. Moreover, this scale has been previously used in several soccer studies [ 28 ]. In addition, the duration of the entire training session and/or match in minutes was multiplied by the RPE to generate the session-RPE (A.U.)…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, this study showed that higher intensity sessions contributed to improved sleep and that longer sleep duration contributed to higher session-RPE (s-RPE) values [ 15 ]. Considering that microcycle demands may vary within each week [ 17 ], data on the relationships between intensity and other wellness variables such as fatigue, muscle soreness, mood and stress is also required to provide useful insights for coaches [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…44 Despite only one study considered energy expenditure, 44 data from professional male soccer players seems to support this findings considering lower intensities in the day before and after the match while higher intensities were found in the middle days of the week. 14…”
Section: Training Intensitymentioning
confidence: 99%
“…10 Although training and match intensity monitoring are well-established research topics in sports sciences, 11 especially in soccer, 12 there is still a gap between genders. Most of the research involving intensity monitoring is focused on men, ranging from youth 13 to professional 14 players. However, over the past decade, there has been an exponential rise in the participation and professionalisation of female athletes.…”
Section: Introductionmentioning
confidence: 99%